Analisis Pengetahuan Tentang Gangguan Menstruasi Dikalangan Akseptor Kb Suntik 3 Bulan - Bardiati Ulfah; Pratiwi Puji Lestari (INVOLUSI: Jurnal Ilmu Kebidanan, 2022)
Background : Injectable contraceptives have several complaints that may occur such as changes in menstruation and no menstruation. Purpose of the study: To describe the knowledge of acceptors of 3-month injectable contraception (DEPO) on menstrual disorders at the Independent Practice Midwife Siti Fatimah Sungai Sipai Martapura. Research method : Using descriptive method with cross sectional approach. Results: The results showed that from 60 respondents, 15 people had good knowledge about menstrual disorders (25%), 20 people had sufficient knowledge (33.4%) and 25 people had less knowledge (41.6%). Conclusion: Injectable family planning acceptors at BPM Siti Fatimah, S.ST Sungai Sipai Martapura still have less knowledge about menstrual disorders.